Assessment of Energy Potential and Benefit under the Ground Source Heat Pump Air Conditioning System in Anqing Area of Eastern China. (9th November 2021) - Zhang, Qing; Li, Yunfeng; Hua, Jian; Niu, Xiaonan; Hou, Lili; Chen, Zongfang; Ge, Weiya
Abstract : Now ground source heat pump is a more efficient way to develop and utilize shallow geothermal energy because it is clean and environmentally friendly and has a relatively low energy cost. In order to optimize the planning layout and geographical space development in the eastern new town of Anqing city, which can realize the transformation and upgrading of real space and urban sustainable development, the exploration for shallow geothermal energy will be carried out in this area, so as to find out the comprehensive thermophysical parameters of the shallow rock-soil body and the heat transfer capacity of the vertical heat exchanger, etc. This paper takes the CBD in the eastern new town of Anqing as an example to provide the basis for the feasibility construction of the ground source heat pump project in the study area and evaluate the economic and environmental benefits of the expected project. According to the simulation test data of 5 working conditions of 4 geothermal exploration holes in the study area, we can clearly know that the energy cost per square meter of the ground source heat pump is 11.8 yuan for a building of one hundred thousand square meters in which the heat removal power is expected to be 9481 kW in summer and 3070 kW in winter. And the annual emission of carbon dioxide, sulfur dioxide, nitrogen oxides, suspended dust, and other air pollutants to the atmosphere can be reduced by 1442.5 t, and the solid waste ash and slag can be reduced by 59.7 t. The annual environmental treatment cost will be saved by 166000 yuan.